A New Audio Steganography System Based on Auto-Key Generator - Kadhim, Inas Jawad (Al-Khwarizmi Engineering Journal, 2012)
Stenography is the art of hiding the very presence of communication by embedding secret message into innocuous looking cover document, such as digital image, videos, sound files, and other computer files that contain perceptually irrelevant or redundant information as covers or carriers to hide secret messages. In this paper, a new Least Significant Bit (LSB) nonsequential embedding technique in wave audio files is introduced. To support the immunity of proposed hiding system, and in order to recover some weak aspect inherent with the pure implementation of stego-systems, some auxiliary processes were suggested and investigated including the use of hidden text jumping process and stream ciphering algorithm. Besides, the suggested system used self crypto-hiding pseudo random key generator. The auto-key generator has purposes to investigate the encryption and embedding processes .The hiding results shows no noise in the stego-wave file after embedding process, also no difference in size is found between the original wave audio file and stego-wave file.